Water can accelerate homogeneous gold catalysis - Stein, Philipp; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2021)
A selection of gold-catalyzed reactions was examined in a kinetic study on the influence of water on the rate constant. Two intramolecular reactions and one intermolecular reaction, which proceed via proton transfer and/or protodeauration steps, were investigated. The kinetic data was collected by GC or 1H NMR spectroscopy. The obtained rate constants provided information about the influence of water in these test reactions. On the basis of the data collected, beyond the commonly assumed tolerance against water, a reaction-promoting influence of water on gold catalysis was identified and kinetically quantified. The results underline that the often-mentioned water-tolerance of gold catalysis not only simplifies these reactions operationally, but in addition even provides better results than a troublesome exclusion of water.
Gesehen am 29.03.2023